The pressure metric on the Margulis multiverse - Ghosh, Sourav (Geometriae dedicata, 2018)
This paper defines the pressure metric on the Moduli space of Margulis spacetimes without cusps and shows that it is positive definite on the constant entropy sections. It also demonstrates an identity regarding the variation of the cross-ratios.